1998
DOI: 10.1136/thx.53.4.274
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profiles of Chinese patients with diffuse panbronchiolitis

Abstract: Background-DiVuse panbronchiolitis (DPB), characterised by progressive sinobronchial sepsis, is well characterised in Japanese subjects but not in other ethnic groups. The experience with DPB in seven Chinese patients is described and the clinical profiles compared with those of Japanese subjects. Methods-Seven Chinese patients (three women; mean (SD) age 48(18.6) years, all never smokers) who attended a teaching hospital centre and fulfilled the diagnostic criteria for DPB were assessed prospectively for clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 30 publications
1
28
1
2
Order By: Relevance
“…DPB was Wrst described in Japanese patients (Homma et al 1983) and subsequently in Koreans (Kim et al 1992) and Chinese (Chu et al 1992;Tsang et al 1998). Sugiyama et al (1990) reported that the frequency of human leukocyte antigen (HLA)-B54 was much higher in Japanese DPB patients than that in the normal population.…”
Section: Introductionmentioning
confidence: 97%
“…DPB was Wrst described in Japanese patients (Homma et al 1983) and subsequently in Koreans (Kim et al 1992) and Chinese (Chu et al 1992;Tsang et al 1998). Sugiyama et al (1990) reported that the frequency of human leukocyte antigen (HLA)-B54 was much higher in Japanese DPB patients than that in the normal population.…”
Section: Introductionmentioning
confidence: 97%
“…It was originally reported in Japan (2). However, an increasing number of cases have been reported in Europe (3,4) and America (5)(6)(7)(8)(9), as well as in Asia (10), including Thailand (11), India (12), and China (13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Suelen tener un curso paralelo al de la EII, con brotes de síntomas respiratorios junto con brotes de la enfermedad digestiva, hecho que ha llevado a plantear la hipótesis de que la enfermedad podría producirse en el pulmón al tener tanto el tubo digestivo como el pulmón un mismo origen embrionario; este hecho se ve reforzado en el caso de las bronquiectasias tras colectomía, donde, tras quitar el órgano diana del proceso inflamatorio, el aparato respiratorio pasa a ser el siguiente en presentar el daño inflamatorio 9 . Las bronquiectasias suelen ser estériles y sólo demuestran un aumento de los neutrófilos en el lavado broncoalveolar 10,11 .…”
Section: Discussionunclassified